INTEGRASI RELATIONSHIP MARKETING DAN NILAI PENDIDIKAN ISLAM DALAM MEMPERTAHANKAN PUBLIC TRUST DI PESANTREN - Iffatul Aimmah; Muhtadi Abdul Mun’im (Penerbit Widina, Widina Media Utama, 2025)
This study analyzes PP. Al-Amien Prenduan's strategy in maintaining public trust through the integration of relationship marketing and Islamic educational values. The approach used is a qualitative case study through observation, interviews, and documentation with open coding, axial coding, selective coding, and triangulation analysis. The results of the study show that the value of trustworthiness is the basis for managing institutional relationships through transparency in digital-based academic and financial systems, routine information delivery, and explanations of the education system from the time of registration. Educational integrity is evident in curriculum evaluation, teacher training, and learning arrangements. Social contributions are seen in da'wah programs, graduate service, zakat services, and pesantren economic units. Communication patterns run through formal channels such as IKBAL, Hiwari, da'wah safaris, as well as informal communication through visits by santri guardians and alumni networks. Problem solving follows the value of islah with tabayyun, functional cooperation, tiered decision-making, evaluation, and strengthening of social cohesion. The novelty of this research lies in the model of integrating Islamic values and relationship marketing, which produces a pattern of public trust management based on values as the basis for developing educational marketing practices in Islamic boarding schools. ABSTRAKPenelitian ini menganalisis strategi PP. Al-Amien Prenduan dalam menjaga kepercayaan publik melalui integrasi relationship marketing dan nilai pendidikan Islam. Pendekatan yang digunakan ialah kualitatif studi kasus melalui observasi, wawancara, dan dokumentasi dengan analisis open coding, axial coding, selective coding, dan triangulasi. Hasil penelitian menunjukkan bahwa nilai amanah menjadi dasar pengelolaan hubungan lembaga melalui transparansi sistem akademik dan keuangan berbasis digital, penyampaian informasi rutin, serta penjelasan sistem pendidikan sejak pendaftaran. Integritas pendidikan tampak dari evaluasi kurikulum, pelatihan guru, dan pengaturan pembelajaran. Kontribusi sosial terlihat dari program dakwah, pengabdian lulusan, layanan zakat, dan unit ekonomi pesantren. Pola komunikasi berjalan melalui saluran formal seperti IKBAL, Hiwari, safari dakwah, serta komunikasi informal melalui kunjungan wali santri dan jaringan alumni. Penyelesaian masalah mengikuti nilai islah dengan tabayyun, kerja sama fungsionaris, keputusan berjenjang, evaluasi, dan penguatan kohesi sosial. Kebaruan penelitian ini terletak pada model integrasi nilai Islam dan relationship marketing yang menghasilkan pola pengelolaan kepercayaan publik berbasis nilai sebagai dasar pengembangan praktik pemasaran pendidikan di pesantren.